2004
DOI: 10.1051/0004-6361:20040150
|View full text |Cite
|
Sign up to set email alerts
|

WR 20a: A massive cornerstone binary system comprising two extreme early-type stars

Abstract: Abstract.We analyse spectroscopic observations of WR 20a revealing that this star is a massive early-type binary system with a most probable orbital period of ∼3.675 days. Our spectra indicate that both components are most likely of WN6ha or O3If * /WN6ha spectral type. The orbital solution for a period of 3.675 days yields extremely large minimum masses of 70.7 ± 4.0 and 68.8± 3.8 M for the two stars. These properties make WR 20a a cornerstone system for the study of massive star evolution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
132
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 18 publications
2
132
0
Order By: Relevance
“…-Two additional examples of very massive stars in elliptical orbits whose large eccentricity made the discovery of their binarity difficult are WR 22 ≡ HD 92 740 (Moffat & Seggewiss 1978;Conti et al 1979;Schweickhardt et al 1999, WN7 + O8-9.5 III:) and HD 93 162 (Gamen et al 2008;Sota et al 2014, O2.5 If*/WN6 + OB). -There are also very massive twin systems in shorter, nearcircular orbits such as NGC 3603-A1 (Moffat et al 2004;Schnurr et al 2008, WN6ha + WN6ha), WR 20a (Rauw et al 2004;Bonanos et al 2004;Crowther & Walborn 2011 we note that σ Ori B is B0.5 V). Why were these systems not discovered earlier?…”
Section: Discussionmentioning
confidence: 63%
“…-Two additional examples of very massive stars in elliptical orbits whose large eccentricity made the discovery of their binarity difficult are WR 22 ≡ HD 92 740 (Moffat & Seggewiss 1978;Conti et al 1979;Schweickhardt et al 1999, WN7 + O8-9.5 III:) and HD 93 162 (Gamen et al 2008;Sota et al 2014, O2.5 If*/WN6 + OB). -There are also very massive twin systems in shorter, nearcircular orbits such as NGC 3603-A1 (Moffat et al 2004;Schnurr et al 2008, WN6ha + WN6ha), WR 20a (Rauw et al 2004;Bonanos et al 2004;Crowther & Walborn 2011 we note that σ Ori B is B0.5 V). Why were these systems not discovered earlier?…”
Section: Discussionmentioning
confidence: 63%
“…However, given that it appears significantly less massive than the WN6ha + WN6ha binary WR20a (m 1 = m 2 = 83 M , Rauw et al 2004;Bonanos et al 2004) we suspect that it will instead evolve to resemble Cyg OB2 #5 and hence to a configuration similar to GCIRS 16SW, composed Negueruela et al (2008), based on published spectral classes and 2MASS JHK S photometry and a DM of 11.3. The continuous lines are non-rotating isochrones for log t = 6.2, 6.3 and 6.4 from Schaller et al (1992) and the dashed line is the log t = 6.4 isochrone in the high-rotation models from Meynet & Maeder (2003).…”
Section: Discussionmentioning
confidence: 99%
“…These observations revealed strong evidence of ongoing star formation activity and underlined the need for a detailed study of the properties of the early-type stars in the cluster core and their impact on the surrounding nebula. On the other hand, WR 20a -one of the two Wolf-Rayet stars in RCW 49 -was found to be a very massive eclipsing binary consisting of two WN6ha stars with individual masses of about 80 M (Rauw et al 2004(Rauw et al , 2005Bonanos et al 2004). Since previous spectroscopic studies revealed only one O6: and six O7: stars, in the cluster core , the existence of a pair of stars that massive was somewhat unexpected.…”
Section: Introductionmentioning
confidence: 96%